Targeted fishes are larger and more abundant in 'no-take' areas in a subtropical marine park. (15th November 2018) - Malcolm, Hamish A.; Williams, Joel; Schultz, Arthur L.; Neilson, Joe; Johnstone, Nicola; Knott, Nathan A.; Harasti, David; Coleman, Melinda A.; Jordan, Alan
Abstract: The influence of 'no take' Marine Protected Areas (MPAs) on abundance and size of fishes varies considerably and the likely benefits are still debated. Meta-analyses reveal findings are biased towards studies in shallower depths suitable for diving surveys. Empirical comparisons in deeper waters, including among areas with differing spatial management, further contribute to understanding of MPA benefits and constraints. We compare length and abundance of commercially and recreationally targeted fishes (and bycatch) among management types within and adjacent to the Solitary Islands Marine Park (SIMP), Australia. Sampling was done on reefs between 25 and 40 m depth in 'no-take' and fished 'partially protected' areas within the marine park and fished areas outside the SIMP, using stereo- Baited Remote Underwater Videos (stereo-BRUVs) at eight, nine, thirteen and fourteen years after these 'no take' areas were established. Four species targeted by fishers: snapper Chrysophrys auratus, grey morwong Nemadactylus douglasi, pearl perch Glaucosoma scapulare, and venus-tuskfish Choerodon venustus, were more abundant and larger in 'no take' zones overall and showed an increase through time in 'no take' relative to both types of fished area. In contrast, there was no distinct pattern of four bycatch species increasing in abundance in 'no-take' areas. Abundances of fish in partially protected areas were similar to fished areas outside the MPA. This study adds empirical evidence to the assertion that 'no take' areas in particular, can contribute to both marine conservation and natural resource management. Graphical abstract: Image 1 Highlights: Higher abundance of key target fish in 'no take' areas. Larger key targeted fish in 'no take' areas. Few differences between fished areas inside and outside MPA. Bycatch species did not show a higher abundance in 'no take' areas.